Optimization of College Students' Employment Prosperity Index System Based on Multiple Logit Models. (12th July 2022) - Xiang, Wei; Hu, Weizhen
Abstract : The employment of university graduates has always been a matter of great concern to educational administrative departments and governments at all levels. EPI (employment prosperity index) is a weather vane that reflects the situation of the labor market, and it is also an important reference for the national economic situation. This paper constructs college students' EPI from different aspects, such as employment environment, employability, employment status, and public service, focuses on the calculation method of college students' EPI, and obtains the general formula for calculating college students' EPI. Based on the data obtained from a university, the EPI system is optimized by using MLM (multinomial logit model). Through empirical research, it is found that EPI, which is optimized by the system, has the function of evaluating the employment environment of college students, which not only provides macroemployment policies for the government but also provides scientific and effective employment service policies for universities.